The deduced probable HLA-C*03:187-associated human leukocyte antigen haplotype (A*24:02-B*35:01-C*03:187-DRB1*11:01) revealed in Taiwanese unrelated hematopoietic bone marrow stem cell donors - Kuo-Liang Yang; Py-Yu Lin (Tzu Chi Medical Journal)
Objective: HLA-C*03:187 is a rare frequency allele in the human leukocyte antigen (HLA)-C locus. The purpose of this investigation is to indicate the ethnicity of C*03:187 and its deduced plausible HLA haplotype in association in Taiwanese unrelated bone marrow stem cell donors. Materials and Methods: A DNA sequence-based typing procedure was used to verify the rare frequency allele C*03:187. Employing group-specific primer sets' polymerase chain reaction was carried out to amplify exons 2 and 3 of HLA-A locus, HLA-B locus, exon 1 to exon 7 of the HLA-C locus, and exon 2 of the HLA-DRB1 locus. The amplified gene products were sequenced employing the BigDye® Terminator Cycle Sequencing Ready Reaction kits in both directions according to the manufacturer's instructions. Results: The DNA sequence of C*03:187 is identical to C*03:03:01:01 from exon 1 to exon 7, except for codon 152 of exon 3 where GAG of C*03:03:01:01 is replaced by GTG in C*03:187. The nucleotide replacement causes one amino acid change to the protein sequence of C*03:03:01:01 at position 152 where glutamic acid (E) is changed to a valine (V) in C*03:187. The deduced plausible HLA haplotype in association with C*03:187 in Taiwanese is as A*24:02-B*35:01-C*03:187-DRB1*11:01. Conclusion: The data on the deduced plausible HLA haplotype in association with the low-frequency C*03:187 allele that we described in this report are valuable for immunogenetics laboratories for reference purposes. In addition, they can be utilized by search coordinators in hematopoietic stem cell transplant programs to determine a strategy for locating compatible donors in unrelated bone marrow donor registries for a patient with this unusual HLA allele.